2018
DOI: 10.1002/jcp.27579
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TAF1, HNF4A, and CALM2 as potential therapeutic target genes for liver fibrosis

Abstract: The molecular mechanism of liver fibrosis caused by hepatitis C virus (HCV) is not clear. The aim of this study is to understand the molecular mechanism of liver fibrosis induced by HCV and to identify potential therapeutic targets for hepatic fibrosis. We analyzed gene expression patterns between high liver fibrosis and low liver fibrosis samples, and identified genes related to liver fibrosis. We identified TAF1, HNF4A, and CALM2 were related to the development of liver fibrosis. HNF4A is important for hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…HNF4a belongs to the transcription factor of nuclear hormone receptor superfamily 2A, which is mainly found in liver, kidney, and intestinal tissues [35][36][37][38]. In lung tissue, the content of HNF4a is low and its positive expression can even be used as a useful marker for difficult diagnosis in small biopsy samples [39].…”
Section: Discussionmentioning
confidence: 99%
“…HNF4a belongs to the transcription factor of nuclear hormone receptor superfamily 2A, which is mainly found in liver, kidney, and intestinal tissues [35][36][37][38]. In lung tissue, the content of HNF4a is low and its positive expression can even be used as a useful marker for difficult diagnosis in small biopsy samples [39].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we screened six hub genes that may be associated with both HCV infection and alcohol consumption, including TAF1, SAT1, PLCB2, FGD1, ARHGAP4, and ARHGEF9. Among them, studies have shown that TAF1 might be a potential therapeutic target gene for liver fibrosis (Ji et al, ), implying its key role in the development of HCC and potential role as a biomarker. SAT1 is a key regulator of AKT/β‐catenin signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins in STAT3 signaling pathway played important roles in HCV infection or HCC (Ji et al, ; Kao et al, ; Qadri et al, ). HCV infection could lead to increasing of HNF1A and HNF4A proteins, which caused upregulation of ABCC2 (Qadri et al, ).…”
Section: Discussionmentioning
confidence: 99%